Wheat response to soil-applied micronutrients and relationships among soil and tissue tests - Majrashi, Mosaed Abdullah (Kansas State University, 2018)
Optimum plant growth under field conditions requires adequate levels of essential nutrients. The objectives of this study were; i) to determine the effect of micronutrient fertilizer application on the concentration of macro and micronutrients in winter wheat plant tissue, and ii) investigate the relationship between soil test parameters and concentration of macro and micronutrients in plant tissue. The study was conducted at six locations in 2012 and 2013 in Kansas. The experimental design consisted of two treatments in a randomized complete block design with three replications. The treatments were applied in field-long strips approximately 364 meters (1,200 feet) long and a minimum of 12 meters (40 feet) wide. The treatments included a fertilized strip and a control strip. The study was initially established to evaluate micronutrients with no P, and K fertilizer applied. The fertilized strips included N, Zn, Mn, Cu (11.2 kgha⁻¹), and B (2.8 kgha⁻¹). Soil samples were collected at planting from points marked with flags located every 30 meters along each strip. Soil samples were collected at the 0 to 15-centimeter depth with 15-20 cores per sample from around each flag in about a five-meter radius. Tissue samples were also collected in a five-meter radius of each flag. Wheat flag leaves were collected at flowering with at least 30 leaves per sample. Soil samples were analyzed for pH, organic matter, soil test phosphorus, potassium, boron, copper, iron, manganese, and zinc. Tissue samples were also analyzed for nitrogen, phosphorus, potassium, sulfur, copper, iron, manganese, and zinc. A complete analysis was done for each location as well as across all study locations using the Proc Mixed procedure in SAS. The micronutrient fertilizer application did not significantly (at P-value level <0.05) influenced tissue N, P, and K but increased S, Zn and Cu tissue concentration across all locations. Manganese tissue concentration was not affected by the application of Mn fertilizer application. Soil test Cu, Fe, and Mn showed good correlation with soil pH and soil test Zn with soil OM. However, only Cu and Mn in the wheat tissue show correlation to soil test for these nutrients. These results suggest that micronutrient concentration in the tissue is governed by multiple soil factors and only partially by DTPA extractable micronutrients. Results from this study also showed that tissue analysis could reflect fertilizer application and availability of micronutrients to the plant. However, there was significant variability in tissue analysis, likely affected by abiotic factors influencing plant nutrient uptake and concentration. While tissue analysis can help as diagnostic tool, producers should be aware of the limitations, and decisions on fertilizer recommendations cannot be based exclusively on tissue test.
Keywords: Wheat; Micronutrients; Soil and tissue, their relationship